The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.2136/sssaj2011.0352
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Soil Phosphorus and Potassium following Real Time Kinematic‐Guided Broadcast and Deep‐Band Placement in Strip‐Till and No‐Till

Abstract: Fertilizer placement may cause non‐uniform nutrient distribution in the soil, making it difficult to determine whole‐field fertility by traditional sampling strategies. Our objectives were to determine P and K distribution after repeated applications in no‐till and strip‐till soils and to develop improved sampling procedures to estimate soil P and K levels on a corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] rotation with crops planted at 76‐cm row spacing. Three trials near Pesotum, IL, received blend… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
33
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 29 publications
7
33
0
Order By: Relevance
“…5). Similar results were reported in previous studies (Fernández and Schaefer, 2012;Mallarino and Borges, 2006). Comparing residual P from NT-BR vs. ST-DB, the results from this study suggest that deep band fertilization has lower potential for runoff and environmental P loses (Hale et al, 2015;Nkebiwe et al, 2016).…”
Section: Tillagesupporting
confidence: 91%
See 1 more Smart Citation
“…5). Similar results were reported in previous studies (Fernández and Schaefer, 2012;Mallarino and Borges, 2006). Comparing residual P from NT-BR vs. ST-DB, the results from this study suggest that deep band fertilization has lower potential for runoff and environmental P loses (Hale et al, 2015;Nkebiwe et al, 2016).…”
Section: Tillagesupporting
confidence: 91%
“…5). These results showed the potential challenges for soil sampling and soil test determination at whole-field scale by traditional sampling strategies (Fernández and Schaefer, 2012). In the long term, plant P uptake and P partitioning between plant parts can also promote a non-uniform re-distribution of P in the soil profile (Clarkson et al, 1978, Xue et al, 2014.…”
Section: Residual Soil Phosphorusmentioning
confidence: 95%
“…Those authors observed no change in soil test P concentrations under NT for broadcast application across all sampling positions with respect to the crop row for the top 30 cm of the soil. In contrast, increases in soil P levels were observed at the crop row relative to interrow positions at maintenance or recommended fertilizer P rates for subsurface-band fertilization (at 15 cm below the soil) (Farmaha et al, 2012;Fernández and Schaefer, 2012) or injection (at 10 cm below the soil) (Duiker and Beegle, 2006). Continuous band applications of P in the same soil volume result in a substantial localized increase in soil P test levels and depletion in the rest of the rooting zone.…”
mentioning
confidence: 88%
“…Evidence of such two-dimensional (2-D) spatial variability, both vertical and horizontal, in NT was highlighted in a 2-yr study under a corn (Zea mays L.) and soybean [Glycine max (L.) Merr.] rotation with crops planted at 76-cm row spacing (Fernández and Schaefer, 2012). Those authors observed no change in soil test P concentrations under NT for broadcast application across all sampling positions with respect to the crop row for the top 30 cm of the soil.…”
mentioning
confidence: 89%
“…The benefits also represent an efficient use of inputs and lower environmental impact. Under CT practices, soil nutrient dynamics are more susceptible to losses in the envi-ronment by soil erosion, losses to the atmosphere, and leaching (Cook and Trlica, 2016;Fernández and Schaefer, 2012;Young et al, 2009). …”
Section: Introductionmentioning
confidence: 99%